SELIMIYE MOSQUE IN NICOSIA - Çelik, Tahir; Eren, Özgür (My University, 1993)
Selimiye Mosque is a great Gothic building situated in Nicosia, Cyprus. It was built as a Cathedral in 13th century. It has a span of the nave vaults of 9m and two aisle vaults each of them of 7m. Ottoman Empire invaded Cyprus in 1570, and converted the Cathedral of Saint Sophia into a Mosque, called Selimiye, and two minarets were added. Because of poor materials and wrong methods of construction, the building was badly damaged by the help of earthquakes many times. However, it was repaired each time, and the building today is in safe conditions. The building is under special attention and had major restoration works after 1970, but still there are some more works to be done to preserve it.
Keywords: SELIMIYE MOSQUE; NICOSIA; CONSTRUCTION; MATERIAL